Alcalase immobilization onto chitosan/glutaraldehyde/tripolyphosphate beads obtained by inverse emulsion technique - Žuža-Praštalo Milena; Milašinović Nikola; Jonović Marko; Kalagasidis-Krušić Melina; Knežević-Jugović Zorica (Chemical Industry and Chemical Engineering Quarterly)
Enzymes immobilization can efficiently solve limitations of their large-scale application, such as stability and reusability. In this study, Alcalase® 2.4L (protease from Bacillus licheniformis) was covalently immobilized onto chitosan beads obtained by inverse emulsion technique using 1.5% (m/v) of chitosan and 0.67% (v/v) or 1.0% (v/v) of glutaraldehyde (CTPP (1.5/0.67) and CTPP (1.5/1.0)). Afterward, the beads were additionally crosslinked by immersion into 10 % (m/v) tripolyphosphate solution. The parameters studied were enzyme loading, enzyme coupling yield, bead diameter, SEM, biocatalyst activity, and FTIR. The beads had adequate enzyme loading and enzyme coupling yield (Pgmax was 117.1 mg/g dry CTPP 1.5/0.67 and 90.1 mg/g dry CTPP 1.5/1.0, and μmax was 96.7% for both carriers). CTPP (1.5/1.00) beads were smaller (diameter 635.2 ±25.2 mm wet/ 230.4±12.5 mm dry beads) and showed a higher specific activity of 20.1 ± 0.23 IU/mgprotein. The immobilized Alcalase® 2.4L was tested for hydrolyzing egg white and soy proteins. Alcalase® 2.4L, covalently attached to CTTP (1.5/1.0) chitosan beads, is a promising choice for industrial processes involving egg white protein hydrolysis, as the enzyme achieved a notable hydrolysis rate of 26.34 ± 0.879% after 195 minutes. Additionally, it remained effective through five successive applications under practical conditions (50°C, pH 8).